Implementation of School-Based Management in Curriculum and Learning Processes: a Literatur Review - Lorensius Amon; M Rajib Bustami (ILIN Institute Makassar, 2021)
This literature review discusses the implementation of school-based management (SBM) in curriculum management and school-based learning adopted by primary and secondary education institutions in Indonesia. The analysis used is descriptive analysis to deepen knowledge about the implementation of SBM. The results of this study indicate that the implementation of SBM so far has met with limited success. To improve the implementation and outcomes of SBM requires increasing the capacity of principals, teachers, and school committees in implementing SBM; improve staff's ability to make operational and instructional changes; and developing the capacity of central and local governments to support schools in implementing SBM. The SBM indicator, planning emphasizes the importance of aspects of the school's vision and mission, changes that occur in the education process, and adjustments to curriculum programs. Organizing is done through the assignment of duties and authority by the principal to personnel. Implementation requires the participation of all school members and supervision to check learning tools, such as teaching materials, lesson plans, and learning media and learning supervision. By implementing SBM, curriculum management and learning processes can be carried out effectively and efficiently, build student character, improve learning achievement, and improve the quality of education.